How the brain learns to read - Sousa, David A. (Thousand Oaks, California : Corwin, a SAGE Company, 2014)
Examines source material on brain research and provides primary and secondary classroom reading strategies for teachers based on the most current findings. There are five core chapters on - what the research tells us, understanding language acquisition, instructional strategies, identifying reading problems, and strategies for resolving reading problems. The book includes a useful glossary of terms integrates brain diagrams to language acquisitions and strategies.
Learning Spoken Language -- Learning to Read -- Teaching Reading for Encoding and Decoding -- Teaching Reading for Comprehension -- Recognizing Reading Problems -- Overcoming Reading Problems -- Reading in the Content Areas -- Putting It All Together.
Previous edition: 2005.
Includes bibliographical references (pages 237-253) and index.
Keywords: Reading; Reading disability -- Physiological aspects; Brain